Analisis Analisis Kesalahan Siswa Kelas VIII SMP dalam Menyelesaikan Soal Cerita Persamaan Linear Satu Variabel Berdasarkan Prosedur Polya - Angel Stepany Rumapea; Yesika T.S. Pardosi; Asni Silitonga (Mandalika Mathematics and Educations Journal, 2025)
This study aims to describe the types and contributing factors of errors made by eighth-grade junior high school students in solving word problems on the topic of Systems of Linear Equations in One Variable (SPLSV) using the Polya procedure framework. The study used a descriptive qualitative approach and was conducted at the UPT SMP Negeri 3 Medan with students in grade VIII-D. The research instrument was a four-item SPLSV word problem test. Data were analyzed based on the four stages of Polya problem-solving: understanding the problem, planning a solution, implementing the solution plan, and rechecking. The results showed that students made errors at all stages of the Polya process. The highest percentage of errors occurred at the rechecking stage (85.8%), followed by the completion stage of planning (84.1%), planning a solution (75.8%), and understanding the problem (45.8%). Factors contributing to errors included low reading literacy skills, weak understanding of mathematical concepts, inability to create mathematical models, and a lack of metacognitive awareness to re-evaluate answers. These findings indicate the importance of learning that emphasizes conceptual understanding and the application of systematic problem-solving steps.